Social Justice and Public Integrity: Evaluation of the Pertamina Corruption Case from the Pancasila Perspective - Evika Fatika Sari; Taritsa Tsalitsatus Sholihah; Hanna Lailatul Islamiyah; Nadya Qanita Nabila; Phylicia Ilunary Nyo; Prisca Kiki Wulandari (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
Corruption that occurs in the BUMN sector such as Pertamina can reflect systemic problems that have damaged public trust and hampered welfare. This study aims to evaluate based on the values ​​of Pancasila, especially the fifth principle regarding social justice. This study uses a descriptive qualitative approach with a case study method on allegations of corruption in the procurement of crude oil. Data were collected through analysis of media documents, journals, laws and regulations, and online forms for students who are actively studying Pancasila. The results of the study show that corrupt practices not only harm the state financially, but also injure the nation's ideological values, especially the principle of social justice. The conclusion of this study emphasizes that the values ​​of Pancasila should be an ethical basis for managing state institutions, not just as a normative slogan.